In search of land and housing in the new South Africa : the case of Ethembalethu - Berrisford, Stephen; World Bank. (Washington D.C. : World Bank, 2008)
This study describes the saga of how one community, instead of squatting in an informal settlement or invading a new plot of land, attempted to buy land legally and build their own houses in a peri-urban area, using their own savings. The Ethembalethu story draws attention to the many challenges that poor people face accessing land and housing in South Africa. The purpose of this case study is to highlight the complex challenges that face poor communities that attempt to secure their constitutionally mandated rights to adequate housing. These challenges stem from inconsistent or inadequate policies and legislation, confusion between the myriad agencies involved, lack of clarity over responsibilities and accountability, lack of capacity of the implementing agencies, the rising costs and delays in accessing building materials, corruption, and the absence of information and training of both government officials and the housing hopefuls. Finally, the case highlights the Not-In-My-Back-Yard (NIMBY) ferocity with which wealthier citizens may still resist change in the new South Africa. This report draws practical lessons from the case study and makes suggestions for reforms. This report is organized as follows. It begins with a narrative of events, starting in 1996 and ending in 2006. It draws the key lessons emerging from this experience. It then investigates the main issues, and suggests reforms and improvements in the following areas: (i) improving access to land; (ii) simplifying and aligning legal procedures; (iii) designing a land and housing program for peri-urban areas; and (iv) reforming the land market. The report concludes with a call for further participatory action research.
Includes bibliographical references.
Also available on the World Wide Web.
Zahid
Keywords: Land use -- South Africa; Land reform -- South Africa; Housing -- South Africa